Enhancing the photocatalytic activity of ZnO nanoparticles for efficient rhodamine B degradation by functionalised graphene nanoplatelets. Issue 1 (January 2015) - Worajittiphon, Patnarin; Pingmuang, Kanlaya; Inceesungvorn, Burapat; Wetchakun, Natda; Phanichphant, Sukon
Abstract: Amine-functionalised graphene nanoplatelets were decorated with ZnO nanoparticles using a hydrothermal method to improve the photocatalytic activity of the ZnO in dye degradation. Nanocomposite characterisations using X-ray diffraction, Raman spectroscopy and transmission electron microscopy reveal effective interactions between the two constituents. The nanocomposite structure contributes to a high specific surface area, which increases the number of active sites, thus improving the light harvesting ability and the electron transfer efficiency and, subsequently, increasing the photogenerated electron–hole pair separation rate, as shown by the UV–vis diffuse reflectance spectroscopy and photoluminescence results. The resultant enhancement in the photocatalytic activity under ultraviolet light is demonstrated via rhodamine B degradations of up to 98.16% within 40 min, an exceptional degradation rate of 0.138 min −1 . The nanocomposite could alternatively be a new class of photocatalyst materials with potential uses in the remediation of polluted water.